Nonlinear and adaptive control systems - Ding, Zhengtao (London, United Kingdom The Institution of Engineering and Technology, 2013)
The book reviews developments in the following fields: nonlinear systems; adaptive systems; state space models; describing functions; advanced stability theory; feedback linearisation; adaptive control of linear systems; nonlinear observer design; backstepping design; disturbance rejection; output regulation; and control applications.
Electronic reproduction.
Keywords: Nonlinear control theory; Adaptive control systems; Control theory; Feedback (Electronics).; Linear systems; Observers (Control theory).; Quasilinearization; Stability; State-space methods; Electronic books